Lamination of electrophotographic prints - Jašúrek, Bohumil; Vališ, Jan; Šrámková, Michaela (University of Novi Sad, 2022)
Lamination of electrophotographic prints is more problematic than lamination of prints from conventional printing techniques as is for example offset printing. The main problem is worse adhesion of laminating films and due to partial or full delamination can occurs when prints are mechanically stressed. Often problem is also creation of optical effect called silvering. The aim of this work was to compare adhesion of two laminating films (PKCCO BOPP Thermal Laminating Film and Derprosa™ Matte Premier) to prints from different electrophotographic printers (e.g. Xerox, Canon, Konica-Minolta). The lamination conditions were as follows: lamination speeds 10 and 20 m/min, application temperature 120 ˚C and lamination pressure 400 kPa. The adhesion of the laminating film was evaluated by a Peel tester 1 hour, 1 day and 14 days after lamination. The quality of the lamination after the grooving and bending test was evaluated visually. The last measured parameter was colour difference between laminated and non-laminated prints and this parameter was evaluated 1 hour and 14 days after lamination.
Termolaminace elektrofotografickýck výtisků
Keywords: lamination; electrophotography; adhesion; peel test; colour difference; grooving; laminace; elektrofotografir; adhese; peel test; barvová odchylka; rýhování